Local coercivity for semilinear elliptic problems - Mendoza Aranda, Jose Miguel (Universidade Federal de São Carlos, 2018)
We study a non-homogeneous semilinear eliptic problem with Dirichlet condition baundary in a bounded domain and we show existence of solution. Also extend the result to the fraccionary laplacian case and to the homogeneous case we give a result of multiplicity. And to the perturbated problem we find more solutions than the original problem.
Keywords: Problemas elítpticos; Equações diferenciais parciais; Métodos variacionais; Teoría de Morse; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ANALISE